2005
DOI: 10.1007/s10592-005-9036-2
|View full text |Cite
|
Sign up to set email alerts
|

Global-scale genetic identification of hammerhead sharks: Application to assessment of the international fin trade and law enforcement

Abstract: The future status of sharks is an issue of widespread conservation concern due to declines in many species in the face of high levels of exploitation to satisfy market demands for products, especially fins. Substantial declines in the large-bodied hammerhead sharks, Sphyrna lewini, S. mokarran and S. zygaena, even in regions where some management occurs, indicate that informed conservation measures are warranted for these circumglobally distributed species. Despite the importance of assessing shark catch and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
149
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(158 citation statements)
references
References 17 publications
(37 reference statements)
5
149
0
4
Order By: Relevance
“…Despite severe sampling constraints associated with limited market access, dried fin samples were obtained from 11 major Hong Kong fin traders (Clarke et al 2006), and species-specific multiplex PCR confirmed that 62 fins were from Sphyrna lewini (Abercrombie et al 2005). Steps were taken during sampling to ensure that each fin came from a different animal (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite severe sampling constraints associated with limited market access, dried fin samples were obtained from 11 major Hong Kong fin traders (Clarke et al 2006), and species-specific multiplex PCR confirmed that 62 fins were from Sphyrna lewini (Abercrombie et al 2005). Steps were taken during sampling to ensure that each fin came from a different animal (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Fins from this mainly coastal, globally distributed, large hammerhead species fetch premium market prices due to their large size and high 'fin needle' content ($ US 100-120 kg -1 ; Abercrombie et al 2005), and this species appears to have collapsed in the western North Atlantic and Gulf of Mexico due to overexploitation (Baum et al 2003, Myers et al 2007). Consequently, western Atlantic S. lewini has been listed as 'Endangered' (EN A2bd+ 4bd) since 2006 on the International Union for the Conservation of Nature's (IUCN) Red List of Threatened Species.…”
Section: Introductionmentioning
confidence: 99%
“…2003;Abercrombie et al, 2005;Clarke et al, 2006), or on mitochondrial gene sequences (Heist and Gould, 1999;Greig et al, 2005). However, these approaches are not only time consuming but also expensive.…”
mentioning
confidence: 99%
“…Species-specific primers provide lowcost, practical molecular tools that may contribute to the reliable identification of commercial species. This tool has the additional advantage, especially in the context of developing countries, of being relatively easily applied (Abercrombie et al, 2005). The molecular techniques currently available have amplified the perspectives for the application of basic genetic tools to the conservation and management of endangered species in these nations (Bestervan der Merwe & Gledhill, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al (2015) has shown the DNA barcoding to be an effective molecular tool for the detection of commercially-valuable species such as the groupers, while Torres et al (2013) successfully applied PCR RFLP and SNP detection techniques to the identification of specimens of E. itajara, E. morio, M. bonaci, and M. marginata. The multiplex PCR technique, based on the COI gene Mendonça et al, 2010) and other mitochondrial (Trotta et al, 2005;Hashimoto et al, 2010;Ravago-Gotanco et al, 2010) and nuclear genes (Shivji et al, 2002;Chapman et al, 2003;Rodrigues et al, 2011), has proven to be an efficient and rapid low-cost tool that is safe and easy to apply (Abercrombie et al, 2005). This technique permits the identification of illegal fishing by the authorities, even when the catches have been processed for consumption, and contribute to conservation practices on a worldwide scale .…”
Section: Introductionmentioning
confidence: 99%